Analisis Penempatan Pegawai pada Badan Pusat Statistik Kabupaten Karawang - Cantika Dwinur Hariri; Uus Mohammad Darul Fadli (Politeknik Kampar, 2024)
This research aims to analyze employee placement. This research method uses a qualitative descriptive method, research that aims to understand the phenomenon of what is experienced by research subjects, namely how employees are placed at the Karawang Regency Central Statistics Agency. The location of this research was carried out at the Karawang Regency Central Statistics Agency office with a population of 35 people and the sample size was 10 people. The results of research on employee placement analysis at the Karawang Regency Central Statistics Agency show that prospective employees who have passed the competency test will be placed in the appropriate positions required. Based on the results of interviews with several employees at the Central Statistics Agency, the placement of employees at the Karawang Regency Central Statistics Agency office has gone well and is in accordance with what is needed. The researchers have carried out the dimensions and indicators of employee placement, it can be concluded that the employees are placed in accordance with the abilities they have and the competencies they have achieved. Placement of employees who pay attention to suitability of knowledge and skills has been proven to have a positive effect on employee performance.